Recellularization of xenograft heart valves reduces the xenoreactive immune response in an in vivo rat model. (11th October 2021) - Bozso, Sabin J; Kang, Jimmy J H; EL-Andari, Ryaan; Fialka, Nicholas; Zhu, Lin Fu; Meyer, Steven R; Freed, Darren H; Nagendran, Jayan; Nagendran, Jeevan
Abstract:  : OBJECTIVES: Our aim was to address the role of autologous mesenchymal stem cell recellularization of xenogenic valves on the activation of the xenoreactive immune response in an in vivo rat model. METHODS: Explanted aortic valve constructs from female Hartley guinea pigs were procured and decellularized, followed by recellularization with autologous Sprague-Dawley rat mesenchymal stem cells. Aortic valve xenografts were then implanted into the infrarenal aorta of recipient rats. Grafts were implanted as either autologous grafts, non-decellularized (NGP), decellularized and recellularized xenografts (RGP). Rats were euthanized after 7 and 21 days and exsanguinated and the grafts were explanted. RESULTS: The NGP grafts demonstrated significant burden of granulocytes (14.3 cells/HPF) and CD3+ T cells (3.9 cells/HPF) compared to the autologous grafts (2.1 granulocytes/HPF and 0.72 CD3+ T cells/HPF) after 7 days. A lower absolute number of infiltrating granulocytes (NGP vs autologous, 6.4 vs 2.4 cells/HPF) and CD3+ T cells (NGP vs autologous, 2.8 vs 0.8 cells/HPF) was seen after 21 days. Equivalent granulocyte cell infiltration in the RGP grafts (2.4 cells/HPF) compared to the autologous grafts (2.1 cells/HPF) after 7 and 21 days (2.8 vs 2.4 cells/HPF) was observed. Equivalent CD3+ T-cell infiltration in the RGP grafts (0.63 cells/HPF) compared to the autologous grafts (0.72 cells/HPF) after 7 and 21 days (0.7 vs 0.8 cells/HPF) was observed. Immunoglobulin production was significantly greater in the NGP grafts compared to the autologous grafts at 7 (123.3 vs 52.7 mg/mL) and 21 days (93.3 vs 71.6 mg/mL), with a similar decreasing trend in absolute production. Equivalent immunoglobulin production was observed in the RGP grafts compared to the autologous grafts at 7 (40.8 vs 52.7 mg/mL) and 21 days (29.5 vs 71.6 mg/mL). CONCLUSIONS: Autologous mesenchymal stem cell recellularization of xenogenic valves reduces the xenoreactive immune response in an in vivo rat model and may be an effective approach to decrease the progression of xenograft valve dysfunction. Abstract : Valvular heart disease is a common diagnosis with an approximate prevalence of 2.5% of the total population having moderate-to-severe valvular heart disease, resulting in significant reduction in the quality of life for those patients affected [1, 2].